Pengaruh Social Media Marketing dan Customer Experience terhadap Customer Loyalty pada Kedai Kopi Yong Bengkalis Pekanbaru - Helin Helin; Mashur Fadli (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Customer loyalty is a commitment held by individuals or groups to buy or support a product or service again on an ongoing basis. The purpose of this study was to determine the effect of social media marketing and customer experience on customer loyalty in customers of Yong Bengkalis Coffee Shop in Pekanbaru. The population of this study were 14,095 customers and a sample of 99 respondents was obtained using purposive sampling technique. This research uses quantitative methods and descriptive statistics with explanatory research models using SPSS 30.0 tools. The output results of data processing state that partially social media marketing has a significant effect on customer loyalty, customer experience has a significant effect on customer loyalty and simultaneously social media marketing and customer experience have a significant effect on customer loyalty in customers of Yong Bengkalis Coffee Shop in Pekanbaru.